The Correlation between Duration and Frequency of Writing Activities on Subjective Complaints of Carpal Tunnel Syndrome - Hana Widyaningtyas; Erna Setiawati; Tanti Ajoe Kesoema (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: In 2020, lectures were passed online due to the pandemic Covid 19, but now it is offline as before. This method has increased hand duration for writing. Using a hand for long and repetitive duration can affect pathological abnormalities on the nerves that lead to complaints such as soreness, pain, numbness, and weakness. Of these symptoms, 90% refer to a pathological disorder named Carpal Tunnel Syndrome (CTS).Objective: To determine the relationship between writing activities and subjective complaints of CTS using research subjects of students of the Department of Medical Science, Faculty of Medicine, Universitas Diponegoro Semarang Indonesia. Methods: This study is analytical with a crosssectional method. CTS complaints were measured Boston Carpal Tunnel Syndrome Questionnaire(BCTS-Q). Data analysis was performed using univariate analysis and Spearman correlation bivariate analysis. Results: 99 respondents fit the criteria that experience subjective complaints of CTS based on the BCTS-Q; 69.7% mild, 4% moderate, and 1% very severe. There was no correlation between duration (p= 0.852), frequency (p = 0.824), and rest time of writing (p = 0.285) with subjective complaints of CTS. It could be the cause of high subjectivity in interpreting the severity of CTS without a physical examination and difficulty in recalling the time they needed to write in one week. Conclusion: There is no relationship between the duration, frequency, and length of rest time of writing and subjective complaints of CTS.